(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Let V4 be an abelian group under multiplication. Let g : E(G) →V4 −1. The vertex magic labeling on V4 is defined as the vertex labeling g∗ : V (G) →V4 such that ), where the product is taken over all edges uv of G incident at v is a constant. If the constant is 1, it becomes a Hefty V4-vertex magic labeling. A graph is said to be Hefty V4-magic graph if it admits a Hefty V4-vertex magic labeling. In this paper we investigate the Hefty V4-vertex magic labeling behaviour of graphs like Bipartite, Complete graph, Cayley graph etc.